The Pathophysiology of Coronary Artery Disease - Staroselsky, Mark; Materia, Angelo; Damera, Ramses R.; Berman, Lorin; Hai, Ofek; Zeltser, Roman; Makaryus, Amgad N. (International Journal of Angiology, 2025)
Cardiovascular disease is among the most prevalent and morbid conditions worldwide. Coronary artery disease (CAD) is an important cause of cardiovascular disease and can range from mild to fatal conditions. There have been advancements within the field of cardiology to help serve patients and improve outcomes related to CAD. A key aspect of this is a fundamental understanding of the pathophysiology of CAD and applying it in multiple disciplines. Clinicians are better equipped to manage their patients and come up with focused treatment plans once they have a solid foundation of the disease. In this review, we aim to highlight the important pathophysiological mechanisms behind CAD to help aid clinician decision-making and foster future advancements to continue to improve outcomes.
Keywords: coronary artery disease; plaque formation; targeted therapies; pathophysiology